2011
DOI: 10.1002/anie.201103945
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Aerobic Oxidative CH Functionalizations: Trends and Mechanistic Insights

Abstract: The selective oxidation of C-H bonds and the use of O(2) as a stoichiometric oxidant represent two prominent challenges in organic chemistry. Copper(II) is a versatile oxidant, capable of promoting a wide range of oxidative coupling reactions initiated by single-electron transfer (SET) from electron-rich organic molecules. Many of these reactions can be rendered catalytic in Cu by employing molecular oxygen as a stoichiometric oxidant to regenerate the active copper(II) catalyst. Meanwhile, numerous other rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
364
0
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,243 publications
(380 citation statements)
references
References 357 publications
(145 reference statements)
10
364
0
6
Order By: Relevance
“…In the following several years, replacing the organometallic reagents with various C-H or X-H nucleophiles to achieve greener oxidative couplings such as R 1 -H/R 2 -M 2 and R 1 -H/R 2 -H dominated the research area, in which numerous outstanding works have been reported [12][13][14][15]. Especially, transition-metal-catalyzed oxidative R 1 -H/R 2 -H coupling with air or O 2 as the oxidant is no doubt an ideal approach for bond formations [16,17].…”
Section: Numentioning
confidence: 99%
“…In the following several years, replacing the organometallic reagents with various C-H or X-H nucleophiles to achieve greener oxidative couplings such as R 1 -H/R 2 -M 2 and R 1 -H/R 2 -H dominated the research area, in which numerous outstanding works have been reported [12][13][14][15]. Especially, transition-metal-catalyzed oxidative R 1 -H/R 2 -H coupling with air or O 2 as the oxidant is no doubt an ideal approach for bond formations [16,17].…”
Section: Numentioning
confidence: 99%
“…On the other hand, the transition-metal-catalyzed sp 2 C-H amination reaction is one of the most demanding procedures to form C-N bonds [36,37]. In recent years, various late transition metal catalysts such as Pd [38][39][40][41], Ru [42], Rh [43], Ir [44], and Cu [45] have been applied in sp 2 C-H bond amination. Within this methodology, Pd-catalyzed intramolecular aza-Wacker-type oxidative reactions represent one crucial route to produce a range of 5-membered N-containing heterocycles [46][47][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…Often these oxidative coupling reactions require synthetic oxidants, expensive catalysts or high temperatures. Therefore, many attempts are made to develop methods that use cheap catalysts, benign conditions and oxygen or air as terminal oxidant 10 . Many organic compounds react slowly with oxygen from air in autoxidation reactions which can functionalize C-H bonds by effectively inserting O 2 , forming a hydroperoxide moiety 11,12 .…”
Section: Introductionmentioning
confidence: 99%